(untitled) (Journal of Academic Research, 2020)
The aim of this paper is to focus on the works of early Muslim scholars and to rebut the assertion that those scholars played no role in the field of linguistics. There were many influential syntactic, morphological, semantic, phonetic and phonological studies. It can be claimed that some of those studies paved the way to some of the recent linguistic analyses. In particular, the paper concentrates on a specific scholar, Ibn jinni, and his phonetic and phonological efforts.